Communicative functions of a promotional genre as a social action / Hajibah Osman - Osman, Hajibah (UPENA, 2006)
This paper discusses the structural construct of a professional genre, university brochures, with the aim of revealing the dynamic nature of genres as social actions. University brochures are considered as a relatively new genre having been introduced only in the last decade due to a change in the university culture as well as in the culture of the 'university's consumers'. The paper attempts to show how genre analysis can successfully be used to guide readers and writers to understand the structural organization of university brochures and the existence of sociocultural factors that influence the organization. Genre analysis also leads to the identification of the multiple communicative functions of university brochures.